2020
DOI: 10.3389/fcell.2020.611735
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Neuronal Calcium Signaling via Store-Operated Channels in Huntington's Disease

Abstract: Huntington's disease (HD) is a progressive neurodegenerative disorder that is characterized by motor, cognitive, and psychiatric problems. It is caused by a polyglutamine expansion in the huntingtin protein that leads to striatal degeneration via the transcriptional dysregulation of several genes, including genes that are involved in the calcium (Ca2+) signalosome. Recent research has shown that one of the major Ca2+ signaling pathways, store-operated Ca2+ entry (SOCE), is significantly elevated in HD. SOCE re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 217 publications
(359 reference statements)
0
25
0
Order By: Relevance
“…Although a few compounds have been shown to stabilize elevations of SOCE in HD models, future studies are necessary to evaluate their potential for HD therapy (Czeredys, 2020). No treatments for HD are currently available, but this disease may be a good candidate for cell replacement therapy because it is characterized by the relatively focal loss of MSNs that is caused by a mutation of HTT (Rosser and Bachoud-Lévi, 2012).…”
Section: Application Of Stem Cell In Hd Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Although a few compounds have been shown to stabilize elevations of SOCE in HD models, future studies are necessary to evaluate their potential for HD therapy (Czeredys, 2020). No treatments for HD are currently available, but this disease may be a good candidate for cell replacement therapy because it is characterized by the relatively focal loss of MSNs that is caused by a mutation of HTT (Rosser and Bachoud-Lévi, 2012).…”
Section: Application Of Stem Cell In Hd Therapymentioning
confidence: 99%
“…No treatments for HD are currently available, but this disease may be a good candidate for cell replacement therapy because it is characterized by the relatively focal loss of MSNs that is caused by a mutation of HTT (Rosser and Bachoud-Lévi, 2012). It was suggested that mHTT disrupts Ca 2+ signaling in MSNs and those changes could be a cause of HD progression (Raymond, 2017;Pchitskaya et al, 2018;Czeredys, 2020). Therefore transplantation of MSN progenitors without a mutation of HTT appears to be beneficial for HD patients.…”
Section: Application Of Stem Cell In Hd Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…At variance with AD, SOCE is elevated in HD [172][173][174][175]. In both in vitro and in vivo models, SOCE pathway is indirectly and abnormally activated by mutant HTT (mHTT) in striatal γ-aminobutyric acid (GABA)ergic medium spiny neurons (MSNs) before symptoms onset, thus highlighting the role of this Ca 2+ current in disease progression [101,176]. In fact, synaptic loss in MSNs was ascribed to SOCE elevation due to increased expression of STIM2, while STIM1 did not appear to be involved [174].…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%
“…Indeed, NMDAR activation triggers Ca 2+ release from ER stores, STIM1 aggregation and SOCE stimulation in diverse experimental contexts [95,179]. Although there is evidence that compounds that stabilize abnormal SOCE may prevent dendritic spine loss in HD, further work is needed to clarify whether therapeutic strategies specifically acting on SOCE components, including STIMs, deserve further scrutiny to reverse Ca 2+ signalling dysregulation in HD [176].…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%